Anatomy, Pathology, and Histology of Duodenum of Dogs Infected with Toxocara Canis - Rahmawati, Indra; Puji Astuti Nussa, Olan Rahayu; Kusuma Wardhani, Lailia Dwi; Sasmita, Rochiman (Jurnal Medika Veterinaria, 2024)
Toxocara canis infection which attacks dogs are often found in Indonesia. This case study aimed to determine the anatomical and histopathological changes of the duodenum of dogs infected with Toxocara canis. The study was carried out on duodenum of dog which had clinical symptoms of weakness and anorexia. The results of macroscopic observations of the duodenum organ revealed white nodules on the serosal wall of the duodenum and worm infestation in the intestinal lumen. The results of histological observations showed there was rupture of the cylindrical epithelium, erosion of the villi, hemorrhage and desquamation of the submucosa and infiltration of inflammatory cells in duodenum. From these results, it can be concluded that the dog was infected with Toxocara canis worm.